КОНЦЕПЦИЯ ПОСТРОЕНИЯ ЕМКОСТНЫХ ЗАРЯДНЫХ УЗЛОВ МАГНИТНО-ПОЛУПРОВОДНИКОВЫХ ГЕНЕРАТОРОВ - Волков, И.В.; Зозулев, В.И.; Шолох, Д.А.; Христо, А.И. (Інститут електродинаміки НАН України, Київ, 2014)
The research results of the standard and proposed capacitive charging nodes for the magnetic pulse semiconductor devices were described. It’s shown that the nodes functionality expanding is the main way for the magnetic pulse semiconductor devices electrodynamics parameters improvement. The concept basic principles for the capacitive charging nodes construction were formulated. References 8, figures 5.